1998
DOI: 10.1002/hep.510270605
|View full text |Cite
|
Sign up to set email alerts
|

Diet and gallstones in italy: The cross-sectional MICOL results

Abstract: Fifteen thousand nine hundred ten men and 13,674 women (age, 30-69 years) were enrolled in an epidemiological survey of the general population, between December 1984 and April 1987. Each participant was submitted to ultrasonography (US) of the gallbladder and completed a food-frequency questionnaire, covering 38 food items. A common portion size was identified and subjects were asked how often each item was consumed. Nutrient intake was computed by multiplying the intake frequency and nutrient content per port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 72 publications
(85 reference statements)
4
42
0
4
Order By: Relevance
“…On the other hand, both case-control [12, 18]and prospective [6, 8, 19, 20]studies consistently showed that alcohol consumption was related to a decreased risk of clinical gallstone or gallbladder disease. A protective association between alcohol and gallstone disease was also observed in several [16, 21, 22, 23, 24], but not all [14], cross-sectional studies based on screening ultrasonography and in an ultrasonography-based prospective study [17]. It is, however, suspected that gastrointestinal symptoms leading to the clinical diagnosis of gallstones may cause a reduction of alcohol use, thereby spuriously resulting in a protective association between alcohol and gallstones [25].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…On the other hand, both case-control [12, 18]and prospective [6, 8, 19, 20]studies consistently showed that alcohol consumption was related to a decreased risk of clinical gallstone or gallbladder disease. A protective association between alcohol and gallstone disease was also observed in several [16, 21, 22, 23, 24], but not all [14], cross-sectional studies based on screening ultrasonography and in an ultrasonography-based prospective study [17]. It is, however, suspected that gastrointestinal symptoms leading to the clinical diagnosis of gallstones may cause a reduction of alcohol use, thereby spuriously resulting in a protective association between alcohol and gallstones [25].…”
Section: Introductionmentioning
confidence: 67%
“…Alcohol use was unrelated to gallstone disease in men and women combined in Germany [14]. In the Italian multicenter study [24], the investigators addressed the association with newly diagnosed gallstones only and reported a protective association between alcohol use and prevalent gallstones in men, but not in women. In a prospective study based on population screening in southern Italy [17], wine consumption was related to a substantial decrease in gallstone risk among men and women combined, whereas beer and spirits were unrelated to the risk.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a population study in Italy, a positive association was observed between high carbohydrate intake and an increased risk of gall stones diagnosed in an ultrasonographic survey. 20 The inconsistency among these studies may be due to lack of long term dietary information, imprecise or non-validated assessment of nutrients, suboptimal study design, small sample size, or different definitions of disease end points.…”
Section: Discussionmentioning
confidence: 99%
“…14 15 Epidemiological studies of carbohydrate consumption and gall stone disease have shown mixed results. [16][17][18][19][20] Although the available evidence indicates that insulin resistance, chronic hyperglycaemia, and associated disorders of lipid metabolism are important predictors of gall stone disease, the relationship between dietary glycaemic load and glycaemic index and the risk of gall stone disease have not been examined.…”
mentioning
confidence: 99%
“…As dietas ricas em proteínas e fibras têm o efeito oposto, protegendo contra o desenvolvimento de cálculos biliares (Kritchevsky & Dlurfeld, 1983;Attili et al, 1998 Vecchia et al, 1994;Kono et al, 2002) enquanto outras mostram associação com a formação de cálculos biliares (Singh et al, 2001;Timmer A et al, 2000).…”
Section: Fatores Dietéticosunclassified